Contractual concept relationships in specialist prosthodontic health services: Hubungan konsep kontraktual dalam pelayanan kesehatan spesialis prostodonsia - Raodah; Eri Hendra Jubhari (Makassar Dental Journal, 2021)
Relationships between doctors and patients in the field of medicine, also known as therapeutic transactions, in which both parties have rights and obligations that must be carried out fairly and in a balanced manner. A contractual notion or agreement, which is a written or oral agreement made by two or more parties, is required for the connection to be balanced. In health care, there are two sorts of legal ties between patients and doctors: therapeutic contracts and relationships governed by laws and regulations. When a first relationship is formed, it begins with a (unwritten) agreement that assumes both parties' wishes would be met once an agreement is reached. Regulatory interactions typically occur because doctors' obligations are imposed by their profession without the requirement for patient permission. In interdependent health services, the contractual idea relationship between doctors and patients can be balanced if each party understands their rights and obligations. Either a lawsuit based on default or an alleged legal infraction is the issue. The plaintiff (patient) must be able to show that the defendant's (doctor's) fault or carelessness caused the patient's injury. Both parties must be aware of their rights and obligations in order for the contractual relationship between a doctor and a patient to be balanced. The most crucial thing to understand about the contractual notion in prosthodontic specialized health services is ethics. Dental ethics is defined as the application of moral concepts and virtues to the profession of dentistry.